Role of the PI3K/AKT signaling pathway in the cellular response to Tumor Treating Fields (TTFields) - Anat Klein-Goldberg; Tali Voloshin; Efrat Zemer Tov; Rom Paz; Lina Somri-Gannam; Alexandra Volodin; Lilach Koren; Lena Lifshitz; Aviv Meir; Ayelet Shabtay-Orbach; Roni Blatt; Shay Cahal; et al. (Cell Death and Disease)
Abstract Tumor Treating Fields (TTFields) are electric fields that induce cancer cell death. Genomic analysis of glioblastoma tumors resected from TTFields-treated patients suggested a potential link between a reduced or absent response to TTFields and activating mutations in the phosphatidylinositol 3-kinase (PI3K) p110α subunit (PIK3CA). Our study aimed to investigate the role of the PI3K/AKT pathway in the response to TTFields. We tested changes in signaling pathways in control versus TTFields-treated U-87 MG glioblastoma, A2780 ovarian carcinoma, and H1299 non-small cell lung cancer (NSCLC) cells using the Luminex multiplex assay, validated by western blot analysis and inhibition assays. We also performed in vivo validation using immunohistochemistry on tumor sections from animals bearing orthotopic N1-S1 hepatocellular, MOSE-L ovarian, or LL/2 lung tumors that were treated with TTFields or sham. Finally, we examined the efficacy of concomitant treatment with TTFields and PI3K inhibitors in cell lines and mouse models. Our findings elucidate the mechanisms driving PI3K/AKT activation following TTFields treatment, revealing that the AKT signaling amplitude increases over time and is influenced by cell-surface and cell-cell interactions. Specifically, focal adhesion kinase (FAK) and N-cadherin were found to promote AKT phosphorylation, activating cell survival pathways. Furthermore, our investigation revealed that pharmacological inhibition of PI3K sensitized cancer cells to TTFields, both in vitro and in vivo. Our research suggests that the PI3K/AKT pathway is involved in cancer cell response to TTFields, and that inhibition of this pathway may serve as a potential therapeutic target for sensitizing cancer cells to TTFields.